The Stray Grains from Fragments in the Rejoined Platforms of Ni-Based Single-Crystal Superalloy - Miao Huo; Chuyue Chen; Hangyue Jian; Wenchao Yang; Lin Liu (Metals, 2023)
Nickel-based single crystal superalloy is the most important material for blade preparation. However, some solidification defects inevitably occur during the process of preparing single-crystal blades through directional solidification. In this study, in order to study the origin of misorientation defects during solidification, a model with rejoined platforms was designed according to the geometry of single-crystal guide vanes. Electron Back-Scattering Diffraction (EBSD) was used to quantify the orientation deviation of the dendrites and identify the solidification defects in the rejoined platforms. The results showed that stray grain defects appeared in the platforms and their misorientation changed gradually, not abruptly. Combined with the simulation results, it was proposed that the stray grains formed as the result of the dendrites fragment, which was induced by solute enrichment in the mushy zone during solidification. Meanwhile, it was accompanied by a obvious dendritic deformation, which was caused by solidification shrinkage stress. This suggested that the fragmentation was induced by multiple factors, among which, the concave interface shape provided favorable conditions for solute enrichment, and the dynamic variability in the local thermal gradient and fluctuations of the solidification rate might play catalytic roles.